Antimicrobial Susceptibility Pattern of Bacterial Isolates from Patients with Chronic Suppurative Otitis Media - Ahmmed, Salah Uddin; Asaduzzaman, AKM; Ahmed, Basir; Alam, Monsur; Kabir, Misbah AL; Akram, Saleh (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Chronic suppurative otitis media (CSOM) is one of the common diseases of the middle ear especially in developing countries. Early and effective treatment based on the knowledge of causative micro-organisms and their antimicrobial sensitivity pattern ensures prompt clinical recovery and possible complications may be avoided. Objectives: This study was done to determine the pattern of bacterial isolates and to detect their antibiogram. Methods: A total of 103 patients clinically diagnosed of CSOM were enrolled in the study and the samples were obtained from each patient using sterile cotton swabs and cultured for bacterial isolates. Antimicrobial susceptibility test of the isolates were performed using Kirby- Bauer disc diffusion method. Results: Among the cases females were more affected than males. Out of the 103 cases, bacteriological investigation revealed that Pseudomonas aeruginosa 42 (44.68%) and Staphylococcus aureus 31(32.97%) were the predominant bacteria. Ciprofloxacin and Ceftazidime revealed high level of sensitivity whereas high resistance rates were observed for Amoxycillin, Gentamicin and Cephalexin. Conclusion: The study concluded that an appropriate knowledge of the etiological agents and antibacterial susceptibility of microorganisms would contribute to a rational use of antibiotics, success of treatment and reduce the complications of CSOM. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 90-95.